A Slippery Slope: the legal enforceability of Islamic finance judgments and awards in foreign jurisdictions - Oseni, Umar Aimhanosi (2013)
The phenomenal growth in the Sharī'ah-compliant assets has tremendously spurred better interactions among financial systems of the East and the West. Islamic finance is gradually becoming a bridge between these two worldviews. In order to further this global integration of Islamic finance products, this paper examines the legal enforceability of Islamic finance judgments and awards in foreign jurisdictions, be it in the Muslim world or western countries, broadly defined. Based on the reciprocity requirement in international law, which is often premised on bilateral or multilateral treatise, and in some cases conventions, there is a wide scope for the enforcement of foreign judgments and awards involving Islamic finance matters. However, draftsmen of sukuk transactions, and other Islamic finance contracts, often express their concerns on the non-enforceability of foreign judgments and awards in some GCC countries especially when the governing law of such sukuk transactions is the English law. Given the fact that this trend places the global Islamic finance industry on a slippery slope, this study however sets out to examine the dynamics of this challenge faced by draftsperson of Islamic finance contracts vis-à-vis two major conventions – Hague Convention on the Recognition and Enforcement of Foreign Judgments in Civil and Commercial Matters (1971) and New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958). Though the current trends seem like a continuum fallacy within the Islamic finance industry, concerted efforts by the stakeholders to introduce reforms are expected to yield sustainable results.